E-commerce as a Potential New Engine for Growth in Asia - Kinda, Tidiane (IMF Working Papers; Working Paper ;, 2019)
The use of e-commerce around the world has accelerated in recent years, with Asia, led by China, spearheading the rise. Using cross-country enterprise survey data, this paper shows that firms engaged in e-commerce have higher productivity and generate a larger share of their revenues from exports than other firms. This is particularly true in Asia, where firms have 30 percent higher productivity and generate about 50 percent more of their revenues from exports. The results presented in this paper are robust to the use of instrumental variables, which highlight possible larger effects of e-commerce on Asian productivity and exports when essential elements are in place for its effective use, such as reliable electricity, telecommunication, and transport infrastructure. Despite the rapid growth of e-commerce in recent years, gaps persist in digital infrastructure and legislation, preventing many Asian countries from fully reaping the potential benefits of e-commerce.